Crystal and solution structural studies of mouse phospholipid hydroperoxide glutathione peroxidase 4. Issue 10 (6th October 2016) - Janowski, Robert; Scanu, Sandra; Niessing, Dierk; Madl, Tobias
Abstract : The crystal structure of mouse phospholipid hydroperoxide glutathione peroxidase 4 solved at 1.8 Å resolution and the first solution structural studies of a glutathione peroxidase protein are reported. Abstract : The mammalian glutathione peroxidase (GPx) family is a key component of the cellular antioxidative defence system. Within this family, GPx4 has unique features as it accepts a large class of hydroperoxy lipid substrates and has a plethora of biological functions, including sperm maturation, regulation of apoptosis and cerebral embryogenesis. In this paper, the structure of the cytoplasmic isoform of mouse phospholipid hydroperoxide glutathione peroxidase (O70325‐2 GPx4) with selenocysteine 46 mutated to cysteine is reported solved at 1.8 Å resolution using X‐ray crystallography. Furthermore, solution data of an isotope‐labelled GPx protein are presented.